Traditional Chinese medicine’s holistic approach: regulating microglia-driven neuroinflammation for the resolution of Alzheimer’s disease - Yu, Jialing; Bao, Xinya; Shan, Chuchu; Yu, Zebin; Yu, Yajie; Wang, Hongying; Zhang, Yuyan (Frontiers in Cellular Neuroscience, 2025)
BackgroundAlzheimer’s disease (AD) is a progressive neurodegenerative disease characterized by cognitive dysfunction, motor abnormalities, and memory disorders, with a persistently high and rising incidence. The pathological features of AD include the extracellular deposition of the amyloid beta peptide (Aβ), the accumulation of neurofibrillary tangles (NFTs), and neuroinflammation. Microglia (MG), the main immune cells in the central nervous system (CNS), can transform into different phenotypes. An imbalance in their phenotypic transformation may induce neuroinflammation and lead to neurological diseases, playing a central role in the onset and progression of AD.PurposeThis article aims to briefly review the key role of microglia-mediated neuroinflammation in the pathogenesis of AD and to summarize and analyze the strategies of traditional Chinese medicine (TCM) for targeting microglia in AD treatment.MethodsLiterature review and analysis were conducted to summarize the role of microglia-mediated neuroinflammation in AD pathogenesis and to collate TCM therapeutic strategies aimed at modulating microglia.Results and conclusionMicroglia-mediated neuroinflammation plays a central role in the pathological progression of AD. TCM demonstrates potential in intervening in AD neuroinflammation by regulating the microglial phenotype and function. These related therapeutic strategies warrant further summary and analysis.